García-Rodríguez, A. & Gómez-Díaz, R. (2016). Lectura Digital Infantil. Dispositivos, Aplicaciones y Contenidos. Cataluña: UOC. 130 pp. ISBN-13: 978-8491164333 / ISBN-10: 8491164332 - Dantas, Taisa (Revista Interamericana de Bibliotecología, 2019)
García-Rodríguez, A. & Gómez-Díaz, R. (2016). Lectura Digital Infantil. Dispositivos, Aplicaciones y Contenidos. Cataluña: UOC. 130 pp. ISBN-13: 978-8491164333 / ISBN-10: 8491164332